(untitled) - Shepherd, Jack (New York, 1941)
This monograph is one of a series of studies constituting a survey of Southeast Asia, prepared for the international secretariat of the institute of Pacific relations.
Keywords: Industries,Southeast Asia,Công nghiệp,Đông Nam Á; Economic conditions,Điều kiện kinh tế; Southeast Asia,Đông Nam Á